(untitled) (The Review of Diabetic Studies, 2024)
People often use mouthwashes to clean their teeth and gums and keep them healthy. Chlorhexidine (CHX) is the best antiseptic, but its side effects, such as changing the color of teeth, changing the taste, and irritating the mucosal lining, make it not good for long-term use. Try a herbal mouthwash instead. It has fewer side effects and more antibacterial, anti-inflammatory, and antioxidant properties. Neem, miswak, green tea, cinnamon, malva, Nigella sativa, and other unique blends are some examples of these kinds of formulations. Recent randomized trials and systematic reviews show that herbal rinses can reduce gingival indices and plaque in the short term just as well as CHX in some areas. This is despite the fact that CHX sometimes works better against gingivitis in some trials. The existing evidence may exhibit bias, constrained sample sizes, insufficient follow-up, and varying herbal formulations. Herbal mouthwashes have shown promise for patients who can’t handle CHX or who only need a short-term adjuvant. However, more and better randomized trials are needed to find out how well they work in the long term and how they affect microbial ecology.